Religious plurality in Africa: A challenge to the church (Acta Theologica)
Christianity has been a priveleged religion in South Africa under the white minority government. However, since the inception of a democratically elected government in 1994 and the passing of the Constitution of the Republic of South Africa, Act 108 of 1996, all religions have politically equal status. Major religions in the country such as Christianity, Islam, Judaism, Hinduism and African Traditional Religion have to learn to live harmoniously with one another and importantly, to cooperate in projects of sociopolitical nature. This article examines religious plurality in Africa and the implications thereof for South Africa. Three missionary paradigms, viz exclusivism, inclusivism and pluralism are analysed after which a theological perspective is offered. The Church has to communicate the gospel of Jesus Christ nonetheless, but leave the dispensing of salvation in terms of Christian eschatology to God.